VD_FINDINFO Arrêt / 2021 / 26 vom 11. Januar 2021 - VD Tribunal cantonal (2021)
PAIEMENT, PRIME D'ASSURANCE-MALADIE, ADMISSION PARTIELLE | 3 al. 1 LAMal, 64a al. 1 LAMal, 64a al. 2 LAMal, 26 al. 1 LPGA, 105b OAMal, 7 al. 2 OPGA